Remote programming of MED-EL cochlear implants: users' and professionals' evaluation of the remote programming experience. - Kuzovkov, Vladislav; Yanov, Yuri; Levin, Sergey; Bovo, Roberto; Rosignoli, Monica; Eskilsson, Gunnar; Willbas, Staffan (Acta Oto-Laryngologica, 2014)
Conclusion: Remote programming is safe and is well received by health-care professionals and cochlear implant (CI) users. It can be adopted into clinic routine as an alternative to face-to-face programming. Objectives: Telemedicine allows a patient to be treated anywhere in the world. Although it is a growing field, little research has been published on its application to CI programming. We examined hearing professionals' and CI users' subjective reactions to the remote programming experience, including the quality of the programming and the use of the relevant technology. Methods: Remote CI programming was performed in Italy, Sweden, and Russia. Programming sessions had three participants: a CI user, a local host, and a remote expert. After the session, each CI user, local host, and remote expert each completed a questionnaire on their experience. Results: In all, 33 remote programming sessions were carried out, resulting in 99 completed questionnaires. The overwhelming majority of study participants responded positively to all aspects of remote programming. CI users were satisfied with the results in 96.9% of the programming sessions; 100% of participants would use remote programming again. Although technical problems were encountered, they did not cause the sessions to be considerably longer than face-to-face sessions.